Consultantship as the Distinction of Local Referendum - A. E. Guziy (Сибирское юридическое обозрение, 2014)
The article deals with the legal status of consultative referendum as well as with the evaluation of the legal nature of consultative referendum from the point of view of federal legislation positions and construction principles of local self-government. The author comes to the conclusion about the substitution of the notions in the local normative law base and offers the ways out of the current situation.